Access and equity programme provision-evaluation in Australian higher education: a what matters approach. Issue 8 (17th November 2018) - Bennett, Anna
ABSTRACT: This article draws on findings from a national review of the evaluation of access and equity initiatives across Australian higher education to argue that utilising responsive mixed methods focused on the values of participants enables crucial understanding of what matters to the people involved. Based on the evidence collected, a "what matters" conceptual guide is provided to assist with programme design and evaluation. The approach enables identification of the multiple complex variables involved in generating programme outcomes that matter to the groups they are intended for. Provision and evaluation processes must be iteratively connected so that they are responsive to changing contexts and needs over time. Key concepts from critical realism and complexity theory are applied to highlight that context, complexity, and temporality are critical elements to incorporate into approaches to provision-evaluation. The "what matters" guide is designed to enable programmes that are accessible, engaging, and valuable to all participants.